Leading Nursing Excellence Through a System Magnet® Program Director Council. Issue 7 (July 2022) - O'Donnell, Lauren; Ambrose, Heather; Barreca, Rebecca; Brooks, Kimberly; Hayden, Margaret; Henry, Connie; Nelson, Kimberly; Stark, Stacy; Watters, Shelley; Wolff, Lauren
Abstract : American Nurses Credentialing Center Magnet ® designation is prestigious to healthcare institutions. Setting the expectation for all hospitals within a system to be Magnet designated is a lofty but achievable goal. Nursing leaders at the University of Pittsburgh Medical Center set organization-wide designation as a goal in 2010. A robust system-wide Magnet Program Directors Council facilitated this effort by standardizing practices and supporting members through the journey.